2020
DOI: 10.1029/2020je006485
|View full text |Cite
|
Sign up to set email alerts
|

A Broad Continuum of Aeolian Impact Ripple Morphologies on Mars is Enabled by Low Wind Dynamic Pressures

Abstract: Aeolian ripples are common in sandy environments on Earth and Mars. On Earth, ripples in sorted dune sands typically are <1 cm high and are erased in high winds. On Mars in similar sands, ripple wavelengths commonly exceed 2 m, with much smaller ripples superimposed. Large Martian ripple sizes and juxtaposition of multiple wavelengths have raised questions about origins and the applicability of terrestrial aeolian physics to different planetary environments. Here, two hypotheses are evaluated for large Martian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

19
162
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(183 citation statements)
references
References 132 publications
(418 reference statements)
19
162
2
Order By: Relevance
“…Ironically (and there is precedent in the eolian business for using the same data, plotted different ways, to support mutually incompatible theories such as those for "booming dunes"; see Lorenz & Zimbelman, 2014), this trend seems incompatible with that predicted by the fluid drag theory (Figure 2). Similarly, Sullivan et al (2020) show that the wind speeds predicted by the fluid drag model to generate observed bedform wavelength would be too low to cause sand to actually move on Mars, so there are some quantitative difficulties with the application of the model here. Lapotre et al's (2016) suggestion of a fluid drag theory was motivated by the two scales of ripples superposed on the Bagnold dunes, "in contrast to the single scale of superimposed terrestrial ripples".…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Ironically (and there is precedent in the eolian business for using the same data, plotted different ways, to support mutually incompatible theories such as those for "booming dunes"; see Lorenz & Zimbelman, 2014), this trend seems incompatible with that predicted by the fluid drag theory (Figure 2). Similarly, Sullivan et al (2020) show that the wind speeds predicted by the fluid drag model to generate observed bedform wavelength would be too low to cause sand to actually move on Mars, so there are some quantitative difficulties with the application of the model here. Lapotre et al's (2016) suggestion of a fluid drag theory was motivated by the two scales of ripples superposed on the Bagnold dunes, "in contrast to the single scale of superimposed terrestrial ripples".…”
mentioning
confidence: 96%
“…The large grains give the system a stronger memory, their being only nudged by their more easily blown sand fellows resulting in a very slow "creep" along the surface. This memory brings additional degrees of freedom and time-dependent phenomena such as pattern coarsening to these dynamical systems (captured nicely in sophisticated models such as that of Sullivan et al, 2020;Yizhaq et al, 2014, andLämmel et al, 2018). The work by Lämmel et al (2018) shows that the intermittent removal of grains is an instrumental part of the megaripple evolution process.…”
mentioning
confidence: 96%
See 3 more Smart Citations